The pleasing hour a novel - King, Lily (New York, NY Atlantic Monthly Press, 1999)
The lyrical memoir of an American au pair girl in France. She is Rosie of New Hampshire who becomes a little too friendly with the man of the family and is banished to a village in Provence to care for an old aunt. But it is so pretty there and she is so appreciated "it does not feel like penitence."